Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae) - Salvador, Rodrigo B.; Jeugd, Henk Van Der; Tomotani, Barbara M. (Zootaxa, 2017)
The convoluted taxonomy of the European Pied Flycatcher, Ficedula hypoleuca ([Pallas], 1764) (Aves: Passeriformes: Muscicapidae) might present a challenge for researchers working in other areas of biology. We present here a historical review of this species’ nomenclature, discuss its generic allocation, type locality, and all its named subspecies. Its purpose is to help to mitigate errors in application of names in other contexts, and also to point out areas in which future work is needed.